Inspired finance : the role of faith in microfinance and international economic development - Looft, Michael; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
By tracing an arc of thought and action from both historical and religious figures up through modern microfinance practitioners, Looft illustrates the many ways religious inspiration continues to remain at the crux of international economic development-while raising compelling questions around God and Mammon working together to help the poor.
Keywords: Finance -- Religious aspects; Microfinance; Charities; Poverty -- Religious aspects; Economic development -- Religious aspects